Selected Aspects of Carlos Mirabelli’s Mediumship - Nahm, Michael (Journal of Scientific Exploration, 2017)
In the present issue of this Journal, Stephen Braude summarized the enigmatic case of Brazilian medium Carlos Mirabelli, who, like many other physical mediums, was hailed as an outstanding genuine medium by some, and regarded as a complete fraud by others. In this article, I present an overview on two aspects of the Mirabelli mediumship. First, I introduce historical material that relates to the context of the somewhat famous visit of biologist and philosopher Hans Driesch at Mirabelli’s in 1928, along with a few comments from my side; and I will then present two apparently little known accounts of sittings that Mirabelli held in 1930 and 1935 in New York. A Commentary on Hans Driesch’s Sitting with Carlos Mirabelli in 1928 After Albert von Schrenck-Notzing published a German summary of a Portuguese book entitled “O Medium Mirabelli” (Mikulasch 1926; Schrenck-Notzing 1927), discussions about Mirabelli commenced in Germany. For example, in a radio talk held on December 13, 1927, Max Dessoir stated that he received a letter from a woman who claimed that Mirabelli, who was now often discussed in periodicals, was already exposed as swindler. According to this woman, Mirabelli was caught faking during a sitting her husband attended – but apparently, no further details were given. This commentary by Dessoir was cited in an article of Christoph Schröder (1928), then editor of the German parapsychological journal Zeitschrift für Psychische Forschung. Schröder, who was on unfriendly terms with Dessoir, then presented a summary of the Mirabelli sitting on August 2, 1928 – the “famous” sitting that Hans Driesch had attended when he visited Brazil and Argentina (Driesch 1930, 1951; see also Braude, this issue). Schröder’s article contained the rather short séance protocol, the text of which was provided by Bernardo Pritze, a German-born director of the exchange department of the Transatlantic German Bank in Sao Paulo (de Goes 1937, p. 210), in whose small villa in a suburb of Sao Paulo the sitting took place (Figure 1). Pritze added a few personal remarks on the events witnessed.